Superlubricity and non-wetting synergistically induced molten salt self-stripping coating

CN122978752APending Publication Date: 2026-10-27LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611163793.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,该发明仅依靠粘结剂本身的低表面能特性降低熔融态焦粒的黏附,并未对高熵硼化物与二氧化铈等填料进行低表面能设计与润湿性调控

Benefits of technology

1、本发明通过对h-BN的空位氧掺杂调节了h-BN的表面缺陷浓度,氧原子取代硼或氮原子进入空位后,能够有效调控h-BN的表面能与电子结构,在保持h-BN本身高导热、高温稳定特性的同时,降低h-BN的表面能,为实现熔融钠盐的非润湿特性提供了结构基础;另一方面,空位氧掺杂后氮化硼的化学活性提升,有利于后续的羟基化改性、功能基团接枝以及与WC与CaF2之间发生共价插层与杂化反应。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978752A_ABST
    Figure CN122978752A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of superlubrication and non-wetting synergistic induction molten salt self-stripping paint, which is composed of the following raw materials in mass fraction: superlubrication and non-wetting synergistic induction molten salt self-stripping hybrid composite powder 40-50 parts, binder 30-40 parts, functional additive 10-15 parts, anhydrous ethanol 20-25 parts;The superlubrication and non-wetting synergistic induction molten salt self-stripping hybrid composite powder is h-BN-WC-CaF2 hybrid composite material with "sandwich" sandwich structure.The obtained coating of the present application has a synergistic mechanism of "superlubrication reduces molten salt adhesion function-non-wetting inhibits molten salt spreading", reduces the interfacial adhesion between molten salt and coating by superlubrication characteristics, inhibits the spreading process of molten salt on the surface of coating by non-wetting characteristics, and spontaneously peels off molten salt on the surface of coating by the synergistic effect of the two, which solves the problem of molten salt contamination and slagging from the root, and meets the use requirements of high-temperature heating surface of coal-fired boiler under different high-temperature working conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of novel materials for high-temperature interface superlubricity and non-wetting protection, and particularly to a superlubricity and non-wetting synergistic induced molten salt self-stripping coating. Background Technology

[0002] During the combustion of high-alkali coal in coal-fired boilers, alkali metals such as sodium and potassium in the coal form low-melting-point alkali metal sulfates and complex sulfates during high-temperature combustion in the furnace. These sulfates exist in a molten state in the central flame combustion zone of the boiler. When these molten alkali metal salts come into contact with the cooler radiant heating surfaces along with the high-temperature flue gas, they rapidly cool and adhere to the surfaces, accumulating and trapping fly ash particles from the flue gas. This process gradually builds up into a hard, difficult-to-remove fouling slag layer. The presence of this fouling slag layer significantly reduces the heat exchange efficiency of the radiant heating surfaces, reduces the furnace ventilation cross-sectional area, and causes an increase in the superheated steam temperature at the boiler outlet. In severe cases, it can lead to tube overheating and rupture, unplanned shutdowns, and other safety accidents, seriously affecting the operational safety and economy of coal-fired boilers.

[0003] Existing technologies for preventing molten salt fouling and slagging in coal-fired boilers mainly fall into four categories: coal modification, operational adjustment, surface cleaning, and coating protection. Among these, coal modification and operational adjustment are limited by the type of coal and the actual operating load of the boiler, and can only alleviate molten salt slagging to a certain extent, failing to solve the fouling problem at its root. Sonic soot blowing and steam soot blowing are post-treatment methods, which are not only costly but also prone to damaging the heating surfaces, shortening their service life. Coating protection is currently the mainstream approach to inhibiting molten salt adhesion and slagging at its root. It involves preparing a protective coating with specific functions on the surface of the heating surface, regulating the interaction between the molten salt and the heating surface at the interface level, thereby reducing the adhesion ability of the molten salt.

[0004] Patent CN 115160835 B discloses a micro / nano multi-scale anti-coking and anti-wear coating, composite material, and its preparation method. It achieves anti-coking performance by synergistically combining compound oxides and compound nitrides, especially hexagonal boron nitride, to reduce the wettability and friction coefficient of the coating with high-temperature liquid or molten slag, thereby reducing molten salt adhesion to a certain extent. However, besides the inherent limitations of hexagonal boron nitride's tendency to agglomerate and disperse, this technology achieves the composite of functional fillers and binders through a simple compounding method, without further modifying or controlling the surface energy and interlayer van der Waals forces of the compound materials such as hexagonal boron nitride. Therefore, it cannot stably construct a coating structure with low surface energy and superhydrophobic molten salt properties, and cannot achieve long-term stability and self-exfoliation of molten salt.

[0005] Patent CN 117511405 B discloses a functional protective coating and its preparation method, in which the anti-coking performance is achieved by introducing polysilazane with low surface energy. When the surface energy of the heated surface is lower than the critical free energy of the molten coke particles, the coke particles cannot adhere to the surface of the heated surface, thus reducing coking. However, this invention only relies on the low surface energy characteristics of the binder itself to reduce the adhesion of molten coke particles, without designing low surface energy and controlling the wettability of fillers such as high-entropy borides and cerium dioxide. On the other hand, this invention does not address the important role of the low coefficient of friction in the thermodynamic properties of molten salt in superlubricity, making it difficult to achieve the effect of "superlubricity-non-wetting" synergistic induction of self-stripping of molten salt and cooled solidified molten salt, and still has certain application limitations.

[0006] In summary, it is impossible to simultaneously achieve stable non-wetting properties and long-term superlubricating properties of superhydrophobic salts through single non-wetting modifications or simple compounding of lubricating components. Furthermore, the synergistic mechanism of "superlubrication reducing molten salt adhesion - non-wetting inhibiting molten salt spreading" is not established, thus failing to achieve self-scraping of molten salt from the coating surface. Therefore, developing a protective coating with a synergistic effect of superlubrication and non-wetting that induces molten salt self-scraping and its preparation method is of great significance for addressing the long-term protection needs of molten salt contamination and slagging on radiant heating surfaces of coal-fired boilers, molten salt tanks in solar thermal power generation, metal smelting cylinder walls, and 3D printing nozzles. Summary of the Invention

[0007] The technical problem to be solved by the present invention is to provide a high-performance super-lubricating and non-wetting synergistic induced molten salt self-stripping coating.

[0008] To solve the above problems, the present invention provides a superlubricating and non-wetting synergistic induced molten salt self-stripping coating, characterized in that: the coating is composed of the following raw materials in parts by weight: 40-50 parts of superlubricating and non-wetting synergistic induced molten salt self-stripping hybrid composite powder, 30-40 parts of binder, 10-15 parts of functional additives, and 20-25 parts of anhydrous ethanol; wherein the superlubricating and non-wetting synergistic induced molten salt self-stripping hybrid composite powder is an h-BN-WC-CaF2 hybrid composite material with a "sandwich" core structure.

[0009] The h-BN-WC-CaF2 hybrid composite material was prepared by the following method: S1. Dry h-BN is placed in a muffle furnace for high-temperature oxygen doping. After natural cooling, h-BN powder with oxygen doping at vacancies and edges is obtained. The h-BN powder with oxygen doping at the vacancies and edges described in S2 is mixed with the modifier solution at a mass ratio of 1:8~12, and then subjected to high-energy ball milling, filtration and drying to obtain h-BN hydroxylated modified powder. S3 adds a mixture of WC and CaF2 powders in a mass ratio of 1:2.1 to a modifier solution, with the mass ratio of the mixed powder to the modifier solution being 1:1.4. After high-energy ball milling, filtration, and drying, WC-CaF2 modified coupling powder is obtained. S4. The h-BN hydroxylated modified powder, the WC-CaF2 modified coupling powder, and an ethanol aqueous solution with a volume concentration of 15% were added to the reaction vessel in a mass ratio of 1:1.5 to 3:5. After hydrothermal reaction, the mixture was naturally cooled, filtered, and vacuum dried to obtain the h-BN-WC-CaF2 hybrid composite material.

[0010] The conditions for high-temperature oxygen doping in step S1 refer to a heating rate of 3~5 ℃ / min for the muffle furnace, a set temperature of 600~850℃, and a holding time of 1.5~2 h.

[0011] The modifier solution in step S2 and step S3 refers to a mixture obtained by uniformly mixing TEOS, PFDTS, and anhydrous ethanol in a mass ratio of 0.15:0.25:1~4.

[0012] The h-BN is a plate-like hexagonal boron nitride with a hexagonal crystal structure, its particle size is controlled at 25~50 μm, and its density is 2.1~2.29 g / cm³. 3 The boron content is >43.6%; the WC is a hexagonal spherical tungsten carbide powder with a particle size of 10~20 μm, a total carbon content of 6.15~6.21%, and a coefficient of thermal expansion of 3.84×10⁻⁶. -6 ~4.5×10 -6 K; The CaF2 is a spherical calcium fluoride powder with a fluorite-type crystal structure, with a particle size controlled at 0.5~1 μm and a density of 3.01~3.18 g / cm³. 3 Its thermal conductivity is 9.71~10 W / (m·K).

[0013] The conditions for high-energy ball milling in steps S2 and S3 are as follows: the ball mill speed is 800~1200 rpm, the ball-to-material mass ratio is 5:1, the anhydrous ethanol to raw material mass ratio is (1.5~2):1, and the ball milling time is 24~36 h; the drying conditions are as follows: the temperature is 90℃ and the time is 12 h.

[0014] The hydrothermal reaction conditions in step S4 refer to a temperature of 180~240℃ and a holding time of 3~4h; the drying conditions refer to a temperature of 80℃ and a time of 10h.

[0015] The binder is a mixed solution obtained by uniformly mixing perhydropolysilazane, magnesium silicate and aluminum phosphate in a mass ratio of 0.1~0.5:10:12.

[0016] The functional additives refer to a mixed solution obtained by uniformly mixing dispersant, defoamer, and leveling agent in a mass ratio of 1:1 to 2:1; the dispersant is one or both of TEGO 752W and TEGO 655; the defoamer is one or both of TEGO845 polyether siloxane defoamer and Efka EFKA 2720 unsaturated polyester defoamer; and the leveling agent is one or both of BYK333 and BYK381.

[0017] The preparation method of the super-lubricating and non-wetting synergistic induced molten salt self-stripping coating as described above is characterized by: firstly, weighing according to the formula, then mixing and dispersing anhydrous ethanol and binder evenly, and then adding h-BN-WC-CaF2 hybrid composite material and functional additives. Using a high-speed disperser, stirring at a speed of 600~1200 r / min for 240~360 min, then dispersing and grinding to a fineness of 15~30 μm using a sand mill or ball mill, and finally filtering through a 100~200 mesh wire mesh to obtain the coating.

[0018] The method for preparing a coating using the coating material described above includes the following steps: (1) The surface of the 15CrMo substrate was sandblasted using a sandblasting equipment to form a uniformly distributed micro-pit structure on the substrate surface, and the surface roughness was Ra 12.5~Ra 3.2. (2) After ultrasonic cleaning for 20-50 minutes, the substrate surface after sandblasting is dried to obtain the treated substrate surface. (3) The super-lubricating and non-wetting synergistic molten salt self-stripping coating is filled into a 1.5 mm diameter spray gun and the coating is sprayed onto the treated substrate surface to obtain a wet film with a thickness of 80~120 μm. (4) The wet film is cured in a muffle furnace at 180℃~220℃ for 3~6 hours to obtain a dry film with a thickness of 30~50 μm.

[0019] The coating prepared by the method described above is characterized in that: the coefficient of friction of the coating is 0.03 to 0.4 in the temperature range of room temperature to 1200°C, and the contact angle of the molten salt on its surface is >150°; the molten salt refers to one or more of NaCl, Na2SO4, Na2CO3, NaHCO3, KCl, and K2SO4 with a melting point of 300 to 1200°C.

[0020] Compared with the prior art, the present invention has the following advantages: 1. This invention adjusts the surface defect concentration of h-BN by doping with vacant oxygen. After oxygen atoms replace boron or nitrogen atoms in the vacancy, the surface energy and electronic structure of h-BN can be effectively controlled. While maintaining the high thermal conductivity and high temperature stability of h-BN itself, the surface energy of h-BN is reduced, providing a structural basis for realizing the non-wetting properties of molten sodium salt. On the other hand, the chemical activity of boron nitride is enhanced after vacant oxygen doping, which is beneficial to subsequent hydroxylation modification, functional group grafting, and covalent intercalation and hybridization reactions with WC and CaF2.

[0021] 2. This invention significantly improves the problems of easy aggregation, poor water dispersibility, and easy sedimentation of WC, h-BN, and CaF2 by hydroxylating WC, high-temperature oxygen-doped h-BN, and CaF2. This greatly enhances their dispersion uniformity in the composite system without damaging the hexagonal crystal structure of WC and h-BN, or the fluorite crystal structure of CaF2. It solves the problem that traditional simple compounding methods cannot stably utilize the low surface energy, superlubricity, chlorine corrosion resistance, low friction coefficient, corrosion resistance, thermal stability, and wear resistance properties of h-BN, WC, and CaF2. Furthermore, the hydroxylating modification of WC, h-BN, and CaF2 provides a large number of reactive sites on the surface and interlayer of h-BN, WC, and CaF2, ensuring the uniform and stable progress of intercalation assembly and hybridization reactions. This avoids phase separation caused by differences in density and specific surface area of ​​h-BN, WC, and CaF2, which would affect the overall uniformity of the material's properties.

[0022] 3. In the hydrothermal intercalation assembly process, the hydroxyl groups in h-BN, WC, and CaF2 promote the bonding reaction between hydroxyl groups and the functional groups of the covalent intercalation solvent, ensuring the structural uniformity of h-BN, WC, and CaF2 during intercalation assembly and hybridization, and improving the interfacial intercalation bonding strength. This effectively avoids the problem of peeling failure during long-term friction caused by weak interfacial bonding. Furthermore, through hydroxylation modification, vacancy defect regulation, and covalent intercalation assembly, the interlayer spacing of h-BN is increased. The increased interlayer spacing reduces the interlayer van der Waals forces and friction coefficient of h-BN, thereby endowing it with stronger self-lubricating properties and low surface energy characteristics.

[0023] 4. The introduction of CaF2 in this invention can further form a lubricating film with low shear strength under high-temperature service conditions, filling the gap in lubrication performance at high temperatures caused by the degradation of h-BN and WC lubricating phases. It can also form a synergistic lubrication effect with h-BN and WC, maintaining the overall superlubricating properties of the coating over a wide temperature range. Simultaneously, CaF2 itself possesses stable chemical inertness and excellent high-temperature corrosion resistance, significantly improving the coating's ability to resist high-temperature molten salt erosion and further enhancing its long-term stability under complex operating conditions. Furthermore, CaF2 can act as a flux to lower the coating's firing temperature, promote sintering and densification, reduce internal porosity defects, and prevent molten salt from penetrating and eroding the coating through pores, thereby improving the overall structural stability and anti-fouling ability of the coating. At the high-temperature interface, the interaction between CaF2 and molten salt in the coating lowers the melting point and viscosity of the molten alkali metal salt, extending the solidification time. This behavior better complements the synergistic properties of superlubricity and non-wetting to achieve self-scraping of the molten salt.

[0024] 5. This invention, through the construction of an h-BN-WC-CaF2 "sandwich" intercalation hybrid structure, forms a synergistic mechanism of "superlubricity reducing molten salt adhesion and non-wetting inhibiting molten salt spreading." The superlubricity reduces the interfacial adhesion between the molten salt and the coating, while the non-wetting property inhibits the spreading process of the molten salt on the coating surface. Together, these two properties enable spontaneous peeling of the molten salt from the coating surface, fundamentally solving the problem of molten salt contamination and slagging. The contact angle of the molten sodium salt on the coating surface is greater than 150°, and the coefficient of friction can be as low as 0.03, meeting the requirements of non-wetting and superlubricity for molten salt self-peeling.

[0025] 6. The preparation method of this invention has low equipment requirements, strong process controllability, and is suitable for large-scale production. The prepared coating can be directly applied to the surface of the radiant heating surface of a coal-fired boiler using conventional processes such as brushing and spraying. It is convenient to apply and has low cost. It has good engineering application prospects for preventing molten salt fouling and slagging and providing long-term protection on high-temperature heating surfaces of coal-fired boilers, molten salt tanks for solar thermal power generation, metal smelting cylinder walls, and 3D printing nozzles. Attached Figure Description

[0026] The specific embodiments of the present invention will be described in further detail below with reference to the accompanying drawings.

[0027] Figure 1 This is a schematic diagram of the h-BN-WC-CaF2 intercalation hybrid composite material in Embodiment 1 of the present invention.

[0028] Figure 2 This is the XRD pattern of h-BN after high-temperature oxygen doping in Embodiment 2 of the present invention.

[0029] Figure 3The contact angle of the superlubricated and non-wetting synergistic induced molten salt self-stripping coating prepared in Example 3 of the present invention with molten NaCl under normal pressure conditions. Detailed Implementation

[0030] A super-lubricating and non-wetting synergistic induced molten salt self-stripping coating is composed of the following raw materials in parts by mass (g): 40-50 parts of super-lubricating and non-wetting synergistic induced molten salt self-stripping hybrid composite powder, 30-40 parts of binder, 10-15 parts of functional additives, and 20-25 parts of anhydrous ethanol.

[0031] The superlubricating and non-wetting synergistic induced molten salt self-exfoliation hybrid composite powder is an h-BN-WC-CaF2 hybrid composite material with a "sandwich" structure. Through oxygen doping, hydroxylation grafting, covalent intercalation, and hybridization at vacancies and edges, it achieves synergistic induced molten salt self-exfoliation by combining "superlubrication to reduce molten salt adhesion" and "non-wetting to inhibit molten salt spreading." The h-BN-WC-CaF2 hybrid composite material exhibits properties such as superhydrophobicity to molten salt, low interlayer van der Waals forces, low coefficient of friction, and high-temperature corrosion resistance.

[0032] The h-BN-WC-CaF2 hybrid composite material was prepared by the following method: S1. Dry h-BN is placed in a muffle furnace for high-temperature oxygen doping. The heating rate of the muffle furnace is 3~5 °C / min, the temperature is set at 600~850 °C, and the holding time is 1.5~2 h. After natural cooling, the h-BN powder with oxygen doped at vacancies and edges is obtained. h-BN is a hexagonal plate-like hexagonal boron nitride with a particle size controlled at 25~50 μm and a density of 2.1~2.29 g / cm³. 3 The boron content is >43.6%.

[0033] The h-BN powder, doped with oxygen at S2 vacancies and edges, was mixed with a modifier solution at a mass ratio of 1:8 to 12 (g / g). The modifier solution was a mixture of TEOS, PFDTS, and anhydrous ethanol at a mass ratio of 0.15:0.25:1 to 4 (g / g / g). High-energy ball milling was performed at 800–1200 rpm, with a ball-to-material mass ratio of 5:1 and an anhydrous ethanol-to-raw material mass ratio of (1.5–2):1, for 24–36 h. After ball milling, the powder was filtered and dried at 90°C for 12 h to obtain the h-BN hydroxylated modified powder.

[0034] S3. A mixture of WC and CaF2 powders with a mass ratio (g / g) of 1:2.1 was added to a modifier solution, and the mass ratio (g / g) of the mixed powder to the modifier solution was 1:1.4. High-energy ball milling was performed at a speed of 800–1200 rpm, a ball-to-material mass ratio (g / g) of 5:1, and an anhydrous ethanol to raw material mass ratio (g / g) of (1.5–2):1. The milling time was 24–36 h. After milling, the mixture was filtered and dried at 90℃ for 12 h to obtain the WC-CaF2 modified coupling powder.

[0035] WC is a hexagonal spherical tungsten carbide powder with a particle size of 10-20 μm, a total carbon content of 6.15-6.21%, and a coefficient of thermal expansion of 3.84 × 10⁻⁶. -6 ~4.5×10 -6 K;CaF2 is a spherical calcium fluoride powder with a fluorite-type crystal structure, with a particle size controlled at 0.5~1 μm and a density of 3.01~3.18 g / cm³. 3 Its thermal conductivity is 9.71~10 W / (m·K).

[0036] S4 adds h-BN hydroxylated modified powder, WC-CaF2 modified coupling powder, and 15% ethanol aqueous solution at a mass ratio of 1:1.5 to 3:5 (g / g / g) to a reaction vessel. After hydrothermal reaction at 180 to 240°C for 3 to 4 hours, the mixture is naturally cooled, filtered, and vacuum dried at 80°C for 10 hours to obtain the h-BN-WC-CaF2 hybrid composite material.

[0037] The binder is a mixed solution obtained by mixing all-hydrogen polysilazane, magnesium silicate and aluminum phosphate in a mass ratio of 0.1~0.5:10:12 (g / g / g).

[0038] Functional additives refer to a mixed solution obtained by uniformly mixing dispersant, defoamer and leveling agent in a mass ratio of 1:1 to 2:1 (g / g / g); the dispersant is one or two of TEGO 752W and TEGO 655; the defoamer is one or two of TEGO 845 polyether siloxane defoamer and Efka EFKA2720 unsaturated polyester defoamer; the leveling agent is one or two of BYK333 and BYK381.

[0039] A method for preparing a synergistically induced molten salt self-stripping coating by superlubricity and non-wetting: First, weigh the ingredients according to the formula. Then, mix and disperse the anhydrous ethanol and binder evenly, and add the h-BN-WC-CaF2 hybrid composite material and functional additives. Use a high-speed disperser to stir at a speed of 600~1200 r / min for 240~360 min. Then, use a sand mill or ball mill to disperse and grind to a fineness of 15~30μm. Finally, filter through a 100~200 mesh screen to obtain the final product.

[0040] The method for preparing a coating using the above-mentioned paint includes the following steps: (1) The surface of the 15CrMo substrate was sandblasted using a sandblasting equipment to form a uniformly distributed micro-pit structure on the substrate surface, and the surface roughness was Ra 12.5~Ra 3.2. (2) After ultrasonic cleaning for 20-50 minutes, the substrate surface after sandblasting is dried to obtain the treated substrate surface. (3) The super-lubricating and non-wetting synergistic molten salt self-stripping coating is filled into a 1.5 mm diameter spray gun and the coating is sprayed onto the treated substrate surface to obtain a wet film with a thickness of 80~120 μm. (4) The wet film is cured in a muffle furnace at 180℃~220℃ for 3~6 hours to obtain a dry film with a thickness of 30~50 μm.

[0041] The resulting coating has a friction coefficient of 0.03 to 0.4 in the temperature range of room temperature to 1200℃, and the contact angle of the molten salt on its surface is >150°; the molten salt refers to one or more of NaCl, Na2SO4, Na2CO3, NaHCO3, KCl, and K2SO4 with a melting point of 300 to 1200℃.

[0042] Example 1 Vacancy defect oxygen doping and hydroxylation modification of S1 h-BN: The dried h-BN was placed into a corundum ceramic boat. The boat containing the h-BN powder was then transferred to a muffle furnace for high-temperature oxygen doping. The muffle furnace was heated at a rate of 3 °C / min, set to 600 °C, and held for 2 h. After natural cooling, the h-BN powder with oxygen doped at vacancies and edges was obtained.

[0043] The h-BN powder, after oxygen doping at vacancies and edges, was mixed with a modifier solution at a mass ratio of 1:8 (g / g). The modifier solution was a mixture of TEOS, PFDTS, and anhydrous ethanol at a mass ratio of 0.15:0.25:1 (g / g / g). High-energy ball milling was performed at 800 rpm, with a ball-to-material mass ratio of 5:1 and an anhydrous ethanol-to-raw material mass ratio of 1.5:1, for 36 h. After ball milling, the powder was filtered and dried at 90℃ for 12 h to obtain the h-BN hydroxylated modified powder.

[0044] Preparation of S2 WC-CaF2 modified coupling powder: A mixture of WC and CaF2 powders with a mass ratio (g / g) of 1:2.1 was added to a modifier solution, and the mass ratio (g / g) of the mixed powder to the modifier solution was 1:1.4. High-energy ball milling was performed at 800 rpm with a ball-to-powder mass ratio (g / g) of 5:1 and anhydrous ethanol to raw material mass ratio (g / g) of 1.5:1. The milling time was 36 h. After milling, the mixture was filtered and dried at 90℃ for 12 h to obtain the final product.

[0045] Wherein: Modifier solution refers to the mixture obtained by mixing TEOS, PFDTS and anhydrous ethanol in a mass ratio of 0.15:0.25:1 (g / g / g).

[0046] Preparation of S3 h-BN-WC-CaF2 hybrid composite material: The h-BN hydroxylated modified powder, WC-CaF2 modified coupling powder, and 15% (v / v) ethanol aqueous solution were added to a reaction vessel at a mass ratio of 1:1.5:5 (g / g / g). The mixture was hydrothermally reacted at 180℃ for 4 hours, then naturally cooled, filtered, and vacuum dried at 80℃ for 10 hours to obtain the final product. A schematic diagram of the structure of this h-BN-WC-CaF2 hybrid composite material is shown below. Figure 1 As shown.

[0047] Preparation of S4 functional coatings: After mixing and dispersing 20g of anhydrous ethanol and 30g of binder evenly, add 40g of h-BN-WC-CaF2 hybrid composite material and 10g of functional additives. Use a high-speed disperser to stir at 600 r / min for 360 min, then disperse and grind to a fineness of 30μm using a sand mill or ball mill, and finally filter through a 100-mesh wire screen to obtain the final product.

[0048] Wherein: the binder refers to a mixed solution obtained by uniformly mixing perhydropolysilazane, magnesium silicate and aluminum phosphate in a mass ratio of 0.1:10:12 (g / g / g).

[0049] Functional additives refer to a mixed solution obtained by mixing EGO 752W, TEGO 845 and BYK333 in a mass ratio of 1:1:1 (g / g / g).

[0050] Preparation of S5 coating: (1) The surface of the 15CrMo substrate was sandblasted using a sandblasting equipment to form a uniformly distributed micro-pit structure on the substrate surface, and the surface roughness was Ra 12.5. (2) The substrate surface after sandblasting is ultrasonically cleaned for 20 minutes and then dried to obtain the treated substrate surface. (3) The super-lubricating and non-wetting synergistic molten salt self-stripping coating is filled into a 1.5 mm diameter spray gun and sprayed onto the treated substrate surface to obtain a wet film with a thickness of 80 μm. (4) The wet film is cured in a muffle furnace at 180°C for 6 hours to obtain a dry film with a thickness of 30 μm.

[0051] Example 2 Vacancy defect oxygen doping and hydroxylation modification of S1 h-BN: The dried h-BN was placed into a corundum ceramic boat. The boat containing the h-BN powder was then transferred to a muffle furnace for high-temperature oxygen doping. The muffle furnace was heated at a rate of 5 °C / min, set to 850 °C, and held for 1.5 h. After natural cooling, the h-BN powder with oxygen doped at vacancies and edges was obtained.

[0052] The h-BN powder, after oxygen doping at vacancies and edges, was mixed with a modifier solution at a mass ratio of 1:12 (g / g). The modifier solution was a mixture of TEOS, PFDTS, and anhydrous ethanol at a mass ratio of 0.15:0.25:4 (g / g / g). High-energy ball milling was performed at 1200 rpm, with a ball-to-material mass ratio of 5:1 and an anhydrous ethanol-to-raw material mass ratio of 2:1, for 24 h. After ball milling, the powder was filtered and dried at 90℃ for 12 h to obtain the h-BN hydroxylated modified powder. Figure 2 This is the XRD pattern of h-BN after high-temperature oxygen doping. Figure 2 It can be seen that the (010) peak in the figure corresponds to the characteristic diffraction peak of B2O3, and the (002) peak of h-BN shifts slightly to the right after oxygen doping, which indicates that oxygen atoms are successfully doped at the interlayer and interface vacancies of h-BN.

[0053] Preparation of S2 WC-CaF2 modified coupling powder: A mixture of WC and CaF2 powders with a mass ratio (g / g) of 1:2.1 was added to a modifier solution, and the mass ratio (g / g) of the mixed powder to the modifier solution was 1:1.4. High-energy ball milling was performed at 1200 rpm, with a ball-to-material mass ratio (g / g) of 5:1 and anhydrous ethanol to raw material mass ratio (g / g) of 2:1. The milling time was 24 h. After milling, the mixture was filtered and dried at 90℃ for 12 h to obtain the final product.

[0054] Wherein: Modifier solution refers to the mixture obtained by mixing TEOS, PFDTS and anhydrous ethanol in a mass ratio of 0.15:0.25:4 (g / g / g).

[0055] Preparation of S3 h-BN-WC-CaF2 hybrid composite material: The h-BN hydroxylated modified powder, WC-CaF2 modified coupling powder, and 15% ethanol aqueous solution were added to a reaction vessel at a mass ratio of 1:3:5 (g / g / g). After hydrothermal reaction at 240℃ for 3 hours, the mixture was naturally cooled, filtered, and vacuum dried at 80℃ for 10 hours to obtain the final product.

[0056] Preparation of S4 functional coatings: After mixing and dispersing 25g of anhydrous ethanol and 40g of binder evenly, add 50g of h-BN-WC-CaF2 hybrid composite material and 15g of functional additives. Use a high-speed disperser to stir at 1200 r / min for 240min, then disperse and grind to a fineness of 15 μm using a sand mill or ball mill, and finally filter through a 200-mesh wire screen to obtain the final product.

[0057] Wherein: the binder refers to a mixed solution obtained by uniformly mixing perhydropolysilazane, magnesium silicate and aluminum phosphate in a mass ratio of 0.5:10:12 (g / g / g).

[0058] Functional additives refer to a mixed solution obtained by mixing TEGO 752W, EFKA 2720 and BYK333 in a mass ratio of 1:2:1 (g / g / g).

[0059] Preparation of S5 coating: (1) The surface of the 15CrMo substrate was sandblasted using a sandblasting equipment to form a uniformly distributed micro-pit structure on the substrate surface, and the surface roughness was Ra 3.2. (2) The substrate surface after sandblasting is ultrasonically cleaned for 50 min and then dried to obtain the treated substrate surface. (3) The super-lubricating and non-wetting synergistic molten salt self-stripping coating is filled into a 1.5 mm diameter spray gun and sprayed onto the treated substrate surface to obtain a wet film with a thickness of 120 μm. (4) The wet film is cured in a muffle furnace at 220°C for 3 hours to obtain a dry film with a thickness of 50 μm.

[0060] Example 3 Vacancy defect oxygen doping and hydroxylation modification of S1 h-BN: The dried h-BN was placed into a corundum ceramic boat. The boat containing the h-BN powder was then transferred to a muffle furnace for high-temperature oxygen doping. The muffle furnace was heated at a rate of 4 °C / min, set to 760 °C, and held for 1.8 h. After natural cooling, the h-BN powder with oxygen doped at vacancies and edges was obtained.

[0061] The h-BN powder, after oxygen doping at vacancies and edges, was mixed with a modifier solution at a mass ratio of 1:10 (g / g). The modifier solution was a mixture of TEOS, PFDTS, and anhydrous ethanol at a mass ratio of 0.15:0.25:3 (g / g / g). High-energy ball milling was performed at 1000 rpm, with a ball-to-material mass ratio of 5:1 and an anhydrous ethanol-to-raw material mass ratio of 1.8:1, for 30 hours. After ball milling, the powder was filtered and dried at 90℃ for 12 hours to obtain the h-BN hydroxylated modified powder.

[0062] Preparation of S2 WC-CaF2 modified coupling powder: A mixture of WC and CaF2 powders with a mass ratio (g / g) of 1:2.1 was added to a modifier solution, and the mass ratio (g / g) of the mixed powder to the modifier solution was 1:1.4. High-energy ball milling was performed at 1000 rpm with a ball-to-material mass ratio (g / g) of 5:1 and anhydrous ethanol to raw material mass ratio (g / g) of 1.8:1. The milling time was 30 h. After milling, the mixture was filtered and dried at 90℃ for 12 h to obtain the WC-CaF2 modified coupling powder.

[0063] Wherein: Modifier solution refers to the mixture obtained by mixing TEOS, PFDTS and anhydrous ethanol in a mass ratio of 0.15:0.25:3 (g / g / g).

[0064] Preparation of S3 h-BN-WC-CaF2 hybrid composite material: The h-BN hydroxylated modified powder, WC-CaF2 modified coupling powder, and 15% ethanol aqueous solution were added to a reaction vessel at a mass ratio of 1:2.5:5 (g / g / g). After hydrothermal reaction at 200℃ for 3.5h, the mixture was naturally cooled, filtered, and vacuum dried at 80℃ for 10h to obtain the final product.

[0065] Preparation of S4 functional coatings: After mixing and dispersing 23g of anhydrous ethanol and 38g of binder evenly, add 46g of h-BN-WC-CaF2 hybrid composite material and 12g of functional additives. Use a high-speed disperser to stir at 1000 r / min for 320min, then disperse and grind to a fineness of 25 μm using a sand mill or ball mill, and finally filter through a 150-mesh wire screen to obtain the final product.

[0066] Wherein: the binder refers to a mixed solution obtained by uniformly mixing perhydropolysilazane, magnesium silicate and aluminum phosphate in a mass ratio of 0.4:10:12 (g / g / g).

[0067] Functional additives refer to a mixed solution obtained by mixing EGO 752W, EFKA 2720 and BYK333 in a mass ratio of 1:1.6:1 (g / g / g).

[0068] Preparation of S5 coating: (1) The surface of the 15CrMo substrate was sandblasted using a sandblasting equipment to form a uniformly distributed micro-pit structure on the substrate surface, and the surface roughness was Ra 6.3. (2) The substrate surface after sandblasting is ultrasonically cleaned for 40 minutes and then dried to obtain the treated substrate surface. (3) The super-lubricating and non-wetting synergistic molten salt self-stripping coating is filled into a 1.5 mm diameter spray gun and sprayed onto the treated substrate surface to obtain a wet film with a thickness of 100 μm. (4) The wet film is cured in a muffle furnace at 200°C for 5 hours to obtain a dry film with a thickness of 45 μm.

[0069] The coatings obtained in Examples 1-3 were subjected to performance tests: [Molten Salt Wettability Test] The contact angle of molten sodium salt on the coating surface under vacuum and normal pressure conditions was tested using a high-temperature wetting angle measuring instrument (including a vacuum pump). The test results show that the coating prepared by this invention exhibits superhydrophobic properties to common molten salts under vacuum and normal pressure conditions, with a contact angle exceeding 150°. Figure 3 The contact angle of the coating obtained in Example 3 with molten NaCl under normal pressure.

[0070] [High Temperature Resistance Test] The coating was placed in an air atmosphere of a box furnace and subjected to a thermal stability test at 1200℃ for 480 hours. The test results show that the coating prepared by this invention has a stable structure under high temperature conditions, and there are no cracks or blistering on the surface.

[0071]

Salt Spray Corrosion Resistance Test

[0072] [Adhesion Test] The coating adhesion was tested using the pull-out method, referring to ASTM D 4541, "Determination of the pull-out strength of coatings using a portable adhesion tester". The test results showed that the coating pull-out strength was ≥6.8 MPa.

[0073] The results are shown in Table 1.

[0074] Table 1 Performance indicators of coatings prepared in Examples 1-3 [Friction Coefficient Test] The friction coefficient of the test samples at high temperature was tested using a high-temperature tribometer, referencing ASTM G133. The test conditions were reciprocating friction, with a normal force of 5 N. The coating samples obtained in Examples 1-3 were fixed on the platform of the high-temperature tribometer. The initial temperature was set to 30℃, the temperature rise rate was 10℃ / min, and the target temperature ranges were set to 750℃ and 1200℃. When the temperature reached the set value, it was held for 1 hour, and then a reciprocating friction test was performed. The friction pair was Al2O3, the slip frequency was 1 Hz, and the test time was 700 s.

[0075] The results are shown in Table 2.

[0076] Table 2 shows the friction coefficients of the coatings prepared in Examples 1-3 at different temperature ranges. As can be seen from Tables 1 and 2, the molten salt self-stripping coating of the present invention, which uses h-BN-WC-CaF2 hybrid composite material as functional filler and has the characteristics of super-lubricity and non-wetting synergistic induction of molten salt self-stripping, not only achieves the self-stripping characteristics of molten salt through good super-lubricity and molten salt non-wetting synergistic induction, but also has excellent adhesion, corrosion resistance and high temperature resistance, which can meet the requirements of high temperature heating surfaces of coal-fired boilers under different high temperature conditions.

Claims

1. A coating that synergistically induces molten salt self-stripping through super-lubrication and non-wetting, characterized in that: The coating is composed of the following raw materials in parts by weight: 40-50 parts of super-lubricating and non-wetting synergistic induced molten salt self-stripping hybrid composite powder, 30-40 parts of binder, 10-15 parts of functional additives, and 20-25 parts of anhydrous ethanol; the super-lubricating and non-wetting synergistic induced molten salt self-stripping hybrid composite powder is an h-BN-WC-CaF2 hybrid composite material with a "sandwich" core structure.

2. The super-lubricating and non-wetting synergistic induced molten salt self-stripping coating as described in claim 1, characterized in that: The h-BN-WC-CaF2 hybrid composite material was prepared by the following method: S1. Dry h-BN is placed in a muffle furnace for high-temperature oxygen doping. After natural cooling, h-BN powder with oxygen doping at vacancies and edges is obtained. The h-BN powder with oxygen doping at the vacancies and edges described in S2 is mixed with the modifier solution at a mass ratio of 1:8~12, and then subjected to high-energy ball milling, filtration and drying to obtain h-BN hydroxylated modified powder. S3 adds a mixture of WC and CaF2 powders in a mass ratio of 1:2.1 to a modifier solution, with the mass ratio of the mixed powder to the modifier solution being 1:1.

4. After high-energy ball milling, filtration, and drying, WC-CaF2 modified coupling powder is obtained. S4. The h-BN hydroxylated modified powder, the WC-CaF2 modified coupling powder, and an ethanol aqueous solution with a volume concentration of 15% were added to the reaction vessel in a mass ratio of 1:1.5 to 3:

5. After hydrothermal reaction, the mixture was naturally cooled, filtered, and vacuum dried to obtain the h-BN-WC-CaF2 hybrid composite material.

3. The super-lubricating and non-wetting synergistic induced molten salt self-stripping coating as described in claim 2, characterized in that: The conditions for high-temperature oxygen doping in step S1 refer to a heating rate of 3~5 ℃ / min for the muffle furnace, a set temperature of 600~850℃, and a holding time of 1.5~2 h.

4. The super-lubricating and non-wetting synergistic induced molten salt self-stripping coating as described in claim 2, characterized in that: The modifier solution in step S2 and step S3 refers to a mixture obtained by uniformly mixing TEOS, PFDTS, and anhydrous ethanol in a mass ratio of 0.15:0.25:1~4.

5. The super-lubricating and non-wetting synergistic induced molten salt self-stripping coating as described in claim 2, characterized in that: The h-BN is a plate-like hexagonal boron nitride with a hexagonal crystal structure, its particle size is controlled at 25~50 μm, and its density is 2.1~2.29 g / cm³. 3 The boron content is >43.6%; the WC is a hexagonal spherical tungsten carbide powder with a particle size of 10~20 μm, a total carbon content of 6.15~6.21%, and a coefficient of thermal expansion of 3.84×10⁻⁶. -6 ~4.5×10 -6 K; The CaF2 is a spherical calcium fluoride powder with a fluorite-type crystal structure, with a particle size controlled at 0.5~1 μm and a density of 3.01~3.18 g / cm³. 3 Its thermal conductivity is 9.71~10 W / (m·K).

6. The super-lubricating and non-wetting synergistic induced molten salt self-stripping coating as described in claim 2, characterized in that: The conditions for high-energy ball milling in steps S2 and S3 are as follows: the ball mill speed is 800~1200 rpm, the ball-to-material mass ratio is 5:1, the anhydrous ethanol to raw material mass ratio is (1.5~2):1, and the ball milling time is 24~36 h; the drying conditions are as follows: the temperature is 90℃ and the time is 12 h.

7. The super-lubricating and non-wetting synergistic induced molten salt self-stripping coating as described in claim 2, characterized in that: The hydrothermal reaction conditions in step S4 refer to a temperature of 180~240℃ and a holding time of 3~4h; the drying conditions refer to a temperature of 80℃ and a time of 10h.

8. The super-lubricating and non-wetting synergistic induced molten salt self-stripping coating as described in claim 1, characterized in that: The binder is a mixed solution obtained by uniformly mixing perhydropolysilazane, magnesium silicate and aluminum phosphate in a mass ratio of 0.1~0.5:10:

12.

9. The super-lubricating and non-wetting synergistic induced molten salt self-stripping coating as described in claim 1, characterized in that: The functional additives refer to a mixed solution obtained by uniformly mixing dispersant, defoamer and leveling agent in a mass ratio of 1:1 to 2:1; the dispersant is one or two of TEGO 752W and TEGO 655; the defoamer is one or two of TEGO 845 polyether siloxane defoamer and Efka EFKA 2720 unsaturated polyester defoamer; the leveling agent is one or two of BYK333 and BYK381.

10. The method for preparing a synergistically induced molten salt self-stripping coating based on superlubricity and non-wetting as described in claim 1, characterized in that: First, weigh the ingredients according to the formula. Then, mix and disperse the anhydrous ethanol and binder evenly, and add the h-BN-WC-CaF2 hybrid composite material and functional additives. Use a high-speed disperser to stir at a speed of 600~1200 r / min for 240~360 min. Then, use a sand mill or ball mill to disperse and grind to a fineness of 15~30μm. Finally, filter through a 100~200 mesh screen to obtain the final product.

11. A method for preparing a coating using the coating material as described in claim 1, comprising the following steps: (1) The surface of the 15CrMo substrate was sandblasted using a sandblasting equipment to form a uniformly distributed micro-pit structure on the substrate surface, and the surface roughness was Ra 12.5~Ra 3.

2. (2) After ultrasonic cleaning for 20-50 minutes, the substrate surface after sandblasting is dried to obtain the treated substrate surface. (3) The super-lubricating and non-wetting synergistic molten salt self-stripping coating is filled into a 1.5 mm diameter spray gun and the coating is sprayed onto the treated substrate surface to obtain a wet film with a thickness of 80~120 μm. (4) The wet film is cured in a muffle furnace at 180℃~220℃ for 3~6 hours to obtain a dry film with a thickness of 30~50 μm.

12. The coating obtained by the method of claim 11, characterized in that: The coating has a coefficient of friction of 0.03 to 0.4 in the temperature range of room temperature to 1200°C, and the contact angle of the molten salt on its surface is >150°; the molten salt refers to one or more of NaCl, Na2SO4, Na2CO3, NaHCO3, KCl, and K2SO4 with a melting point of 300 to 1200°C.

Citation Information

Patent Citations

  • A micro / nano multi-scale anti-coking and anti-wear coating, composite material and its preparation method

    CN115160835B

  • Functional protective coating and preparation method thereof

    CN117511405B